I'm sorry, my what?. (27th April 2022) - Friginal, Eric
Abstract : This paper explores caller clarification sequences in outsourced call center interactions, with the goal of categorizing distinguishable causes or reasons for their occurrence, as identified by third-party evaluators – i.e., raters who are not participants in the call. Caller clarifications are questions, requests, or follow-up statements raised by a caller after a call-taker's turn while providing information or a procedure during call center interactions (Friginal, 2009a). These potentially unnecessary caller clarifications should have been avoidable if both speakers had been able to communicate and process simplified information effectively. Data were collected from a corpus of transactions, with 545 audio files from the same number of unique Filipino call-takers communicating with customers from the U.S. (N = 578, 511 words). Results show that there are 2.051 caller clarifications per 1, 000 words in the corpus, based on a total of 1, 186 raw instances of caller clarifications. Implications for agent training, the framework of analyzing and categorizing caller clarification, and understanding the nature of intercultural business communication are discussed.